Technology, art and education: The development of the digital game Heróis Capixabas as an educational support tool - Afonso, Maria Carolina Martins; Cirillo, José (Farol, 2026)
With the aim of establishing and developing a cultural and educational support tool, this research focuses on the creation of the digital game Heróis Capixabas, aimed at the historical and artistic dissemination of public monuments in Espírito Santo. The study explores the use of Information and Communication Technologies (ICTs) in art education and bases its methodology on bibliographic research and game development. As an initial result, a visual novel divided into three chapters was conceived, with each chapter dedicated to a specific piece of public art from Espírito Santo. The first chapter—which covers the origins of the bust of Soldier Aldomário Falcão—is currently complete; upon the project's full completion, it is expected to contribute to the appreciation of Espírito Santo's cultural heritage and to the integration of technology, art, and education.
Keywords: education; digital games; art from Espírito Santo; ICTs